2005
DOI: 10.1128/iai.73.9.6091-6100.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Expression Profiling in Malaria Infection Reveals Transcriptional Changes Associated with Lethal and Nonlethal Outcomes

Abstract: High-density oligonucleotide microarrays are widely used to study gene expression in cells exposed to a variety of pathogens. This study addressed the global genome-wide transcriptional activation of genes in hosts infected in vivo, which result in radically different clinical outcomes. We present an analysis of the gene expression profiles that identified a set of host biomarkers which distinguish between lethal and nonlethal blood stage Plasmodium yoelii malaria infections. Multiple biological replicates sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 36 publications
5
25
0
Order By: Relevance
“…S3). Although these response patterns such as up-regulation of proinflammatory pathways largely agreed with those of previous microarray expressional profiling studies (8,36,37), our results clearly showed strainspecific responses and complex disease phenotypes/pathology that were greatly influenced by parasite genetic background. We therefore focused our investigation on the role of the IFN-I and putative CD14 signaling responses in the control of parasitemia and pathogenesis.…”
Section: Parasitemia and Pathology In Mice Infected With N67 And N67csupporting
confidence: 90%
“…S3). Although these response patterns such as up-regulation of proinflammatory pathways largely agreed with those of previous microarray expressional profiling studies (8,36,37), our results clearly showed strainspecific responses and complex disease phenotypes/pathology that were greatly influenced by parasite genetic background. We therefore focused our investigation on the role of the IFN-I and putative CD14 signaling responses in the control of parasitemia and pathogenesis.…”
Section: Parasitemia and Pathology In Mice Infected With N67 And N67csupporting
confidence: 90%
“…Because reticulocytes are the sole source of hemoglobin mRNA, this finding suggested a possible reduction in the circulating-reticulocyte count. This possibility is consistent with previous reports of impaired erythropoiesis in mice infected with lethal murine malaria strains (7,54) and in clinical cases of severe malaria (27). To further investigate the possible implications of the reduction in hemoglobin chain expression in ECM, we measured the expression of hemoglobin ␣1 chain protein in the brain tissue.…”
Section: Resultssupporting
confidence: 73%
“…Genome-wide expression profiling is being increasingly applied to dissect the complex details of the host response to malaria infection [10-16]. Delahaye et al .…”
Section: Introductionmentioning
confidence: 99%